Teacher-Made Materials Based on Meaningful Learning to Foster Writing Skills. - Mosquera, Duvan (Colombian Applied Linguistics Journal, 2023)
This qualitative action research study explores the contribution of teacher-made materials based on meaningful learning to the development of tenth graders’ writing skills. It was carried out with 35 students at a state-funded school in Florencia - Caquetá, Colombia. The instruments used for data collection were students’ artifacts, teacher’s field notes, and a focus group interview. The findings evince that the implementation of well-informed teacher-made materials based on a Materials Development (MD) framework contributes to the development of the learning activities and fosters language learning and use. Besides, meaningful learning occurs as a result of contextualizing content and localizing and personalizing experiences in the learning activities proposed in the workshop to engage students in their completion. Moreover, the students’ writing skills enhance by scaffolding the construction of their texts through the process approach procedures and the cooperative work, as the learning approach that underpinned the development of the writing activities. Finally, giving and receiving feedback served as the source of learner-learner and teacher-learner identification of the state of progress in students’ writings.